IDENTIFIKASI POTENSI WISATA KULINER DI KOTA PANGKALPINANG - Febryola Indra; Juliana Juliana; Nova Bernedeta Sitorus (Jurnal Pariwisata Pesona, 2021)
The diversity of culinary tourism in Pangkal Pinang makes these culinary specialties have a significant potential to be exploited as supporting services in the development of culinary tourist potential. Culinary tourism is an option in addition to other sorts of tourism that visitors to Pangkal Pinang are already familiar with, such as cultural tourism, nature tourism, and marine tourism. This study intends to identify culinary tourism items based on native food ingredients present in Pangkal Pinang City, as well as challenges encountered in the process of establishing Pangkal Pinang City-specific culinary tourism. Culinary tourism is one of the attractions for both domestic and foreign tourists who want to sample various varieties of local cuisine, particularly in Pangkalpinang City. It is also envisaged that it will stimulate the expansion of the creative sector, particularly those relating to culinary tourism, particularly in Pangkalpinang City. The goal of this study is to find local food-based culinary tourism that has the potential to promote culinary tourism in Pangkalpinang City. so that it can look for goods with the potential to be developed from these local food ingredients and study the growth of local food ingredients in Pangkalpinang City This is a descriptive study that employs both primary and secondary data. According to the findings, there are 12 different types of culinary tourist goods based on local food ingredients found in Pangkalpinang City.